The average rate of change for the function f(x) can be calculated from the following equation
![(f( x_(2))-f( x_(1) ))/( x_(2) - x_(1) )](https://img.qammunity.org/2019/formulas/mathematics/high-school/r4ya1uryp6meyp1srx3pygq7thaqyv5cmf.png)
By applying the last formula on the given equations
(1) the first function f
from the table f(3π/2) = -2 and f(2π) = 0
∴ The average rate of f =
![(f(2 \pi)-f( (3 \pi)/(2) ))/(2 \pi - (3 \pi)/(2) ) = (0-(-2))/( (\pi)/(2) )= (2)/( (\pi)/(2) ) = (4)/(\pi)](https://img.qammunity.org/2019/formulas/mathematics/high-school/k8u8hyeoucvnkyb5kucl2u047r5ru4ek91.png)
(2) the second function g(x)
from the graph g(3π/2) = -2 and g(2π) = 0
∴ The average rate of g =
![(g(2 \pi)-g( (3 \pi)/(2) ))/(2 \pi - (3 \pi)/(2) ) = (0-(-2))/( (\pi)/(2) )= (2)/( (\pi)/(2) ) = (4)/(\pi)](https://img.qammunity.org/2019/formulas/mathematics/high-school/n21w2ar3gd1fflp264o6m4fuafqkgb61il.png)
(3) the third function h(x) = 6 sin x +1
∴ h(3π/2) = 6 sin (3π/2) + 1 = 6 *(-1) + 1 = -5
h(2π) = 6 sin (2π) + 1 = 6 * 0 + 1 = 1
∴ The average rate of h =
By comparing the results, The
function which has the greatest rate of change is h(x)
So, the correct answer is option C) h(x)